Economies of scale and scope in the provision of diagnostic techniques and therapeutic services in Portuguese hospitals - Gonçalves, Ricardo (2010)
This paper analyses the provision of auxiliary clinical services that are typically carried out within the hospital. We estimate a exible cost function for the three most important (cost- wise) diagnostic techniques and therapeutic services in Portuguese hospitals: Clinical Pathology, Medical Imaging and Physical Medicine and Rehabilitation. Our objective in carrying out this estimation is the evaluation of economies of scale and scope in the provision of these services. For all services, we nd evidence of ray economies of scale and some evidence of economies of scope. These results have important policy implications and can be related to the ongoing discussion of where and how should hospitals provide these services.